Temporal characteristics of duration of daily activity before and after heart failure hospitalizations in a large real-world population of patients with cardiovascular implanted electronic devices. (14th October 2021) - Sarkar, S; Koehler, J
Abstract: Background: Diagnostic parameters measured in implantable cardioverter defibrillators (ICD) and cardiac resynchronization therapy defibrillators (CRTD) have been shown to change before and after heart failure (HF) events with fluid overload. Purpose: We investigated the temporal characteristics of device measured daily activity duration before and after HF events in a large real-world cohort of patients with ICD/CRTD devices. Methods: We linked a de-identified database of aggregated electronic health record (EHR) data (2007–2017) to a manufacturer's device database with continuous diagnostic monitoring data. Patients with ICD/CRTD implants with HF diagnostic feature were included for this study. Device accumulates the total number of active minutes during a 24-hour period with an active minute defined as total number of accelerometer fluctuations reaching a threshold during the minute. HF event was defined as an inpatient, emergency department, or observation unit stay in a hospital with primary diagnosis of HF and intravenous diuretics administration. Temporal ensemble average of daily duration of activity in the 60 days pre and post HF events were compared between HF events with and without readmission within 60 days and with periods with no HF events during follow-up. Results: A total of 17, 886 patients with 1.8±1.2 years of follow-up met inclusion criteria. The average age of patients was 66.6±12.3 years, with 72% being males, and 51% with ICD devices. The average daily duration of activity in HF events with and without readmission and with no events is shown in Figure. A total of 1174 patients had 1425 HF events with no readmission for HF within 60 days and 282 patients had 295 HF events which were followed by readmission for HF within 60 days. A total of 17, 839 patients had no HF events over 86, 858 follow-up months. The 7-day average activity duration decreased by >10 minutes in a large proportion of patients in the 30-day period before HF event compared to 30-day periods with no events (43% vs 34%; Odds Ratio: 1.52; p<0.001). A 7-day average activity duration increase of >10 minutes from admission to 30 days after admission happens in a smaller proportion of HF events with versus without HF readmission within 60 days of index admission (24% vs 31%; Odds Ratio: 0.7; p<0.001). Conclusions: In a large real-world population of patients with ICD/CRTD devices, the average daily activity duration reduces before HF events. Re-admissions are more likely in patients with smaller increase in activity duration post discharge. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Medtronic Plc